Preservation of the Photoreceptor Inner/Outer Segment Junction in Dry Age-Related Macular Degeneration Treated by Rheohemapheresis - Eva Rencová; Milan Bláha; Jan Studnička; Vladimír Bláha; Miriam Lánská; Ondřej Renc; Alexander Stepanov; Věra Kratochvílová; Hana Langrová (Journal of Ophthalmology)
Aim. To evaluate the long-term effect of rheohemapheresis (RHF) treatment of age-related macular degeneration (AMD) on photoreceptor IS/OS junction status. Methods. In our study, we followed 24 patients with dry AMD and drusenoid retinal pigment epithelium detachment (DPED) for a period of more than 2.5 years. Twelve patients (22 eyes) were treated by RHF and 12 controls (18 eyes) were randomized. The treated group underwent 8 RHF standardized procedures. We evaluated best-corrected visual acuity, IS/OS junction status (SD OCT), and macular function (multifocal electroretinography) at baseline and at 2.5-year follow-up. Results. RHF caused a decrease of whole-blood viscosity/plasma viscosity at about 15/12%. BCVA of treated patients increased insignificantly P=0.187 from median 74.0 letters (56.2 to 81.3 letters) to median 79.0 letters (57.3 to 83.4 letters), but it decreased significantly from 74.0 letters (25.2 to 82.6 letters) to 72.5 letters (23.4 to 83.1 letters) in the control group P=0.041. The mfERG responses in the region of eccentricity between 1.8° and 7° were significantly higher in treated patients P=0.04. Conclusions. RHF contributed to sparing of photoreceptor IS/OS junction integrity in the fovea, which is assumed to be a predictive factor for preservation of visual acuity.